2018
DOI: 10.4102/sajems.v21i1.1756
|View full text |Cite
|
Sign up to set email alerts
|

Ethical practices of small and medium-sized enterprises in developing countries: Literature analysis

Abstract: Background: There is increasing pressure on business organisations to behave ethically, in addition to running their operations in the most economical, efficient and effective manner possible to increase performance. Customers have also become increasingly mindful of the reputation of the businesses they patronise. Small and medium-sized enterprises (SMEs) have become the worst affected since they lack the funds, strategic information and relevant alliances to implement ethical practices. Aim: This article aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 16 publications
1
30
0
1
Order By: Relevance
“…The same study also revealed the expectation that the role of business ethics will expand in the future (Sroka & Lőrinczy, 2015). Some studies have found that business ethics has a positive effect on business competitivity (Turyakira, 2018), brand loyalty and trust (Pivato et al, 2007), and business trustworthiness and dignity (Sroka & Szántó, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 68%
See 1 more Smart Citation
“…The same study also revealed the expectation that the role of business ethics will expand in the future (Sroka & Lőrinczy, 2015). Some studies have found that business ethics has a positive effect on business competitivity (Turyakira, 2018), brand loyalty and trust (Pivato et al, 2007), and business trustworthiness and dignity (Sroka & Szántó, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 68%
“…Pivato et al (2007) state that a company's social contribution builds trust, which is reflected in a positive impact on brand loyalty. In a similar vein, Turyakira (2018) concludes that in order to be competitive in the market and protect their business interests, business organisations and managers must learn to behave ethically. This also relates to other organisational issues such as the utilisation of natural resources, the creation of jobs and the payment of taxes.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Besides, the provisions of the legal system set the platform for effective recognition of operational boundaries among business in the Nigerian economy (Ufua, 2019). As a result of this, practicing SMEs are to be aware and cautious about the end to end effects of their decisions and actions in the process of their operational practices in the sector (Turyakira, 2018). This draws the attention of practicing SMEs to ethical frames that covers their operational process (Ogundele et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…This definition envisages a situation in which an entity, person or organisation, is ideally compatible with existing authority legitimately established. The view is that compliance should not only come from avoiding perceived negative consequences of breach but from a state of mind that believes it's a good thing to comply (Turyakira, 2018). This is perhaps what Okafor (2011) and Riley (2012) had in mind when they expressed compliance as conducting activities in a morally upright manner with positive observable behaviour.…”
Section: Theoretical Review On Compliancementioning
confidence: 98%